Work-Family Conflict, Work- and Family-Role Salience, and Women's Well-Being - Noor, Noraini M. (Heldref Publications, 2004)
The author considered both the direct effect and the moderator effect of role salience in the stress-strain relationship. In contrast to previous studies that have examined the effects of salience on well-being within specific social roles, the present study focused on the work-family interface. From a sample of 147 employed English women with children, the present results of the regression analyses showed that both effects are possible, depending on the outcome measures used. The author observed a direct effect of role salience in the prediction of job satisfaction; work salience was positively related to job satisfaction, over and above the main-effect terms of work-interfering-with-family (WIF) conflict and family-interfering-with-work (FIW) conflict. In contrast, the author found a moderator effect of role salience and conflict for symptoms of psychological distress. However, contrary to predictions, the author found that work salience exacerbated the negative impact of WIF conflict, rather than FIW conflict, on well-being. The author discussed these results in relation to the literature on work-family conflict, role salience, and the issue of stress-strain specificity.